MODES OF READING AND USE OF AN "ARCHIVE OF REPRESSION” IN THE SCIENTIFIC-ACADEMIC FIELD - Colman, Alex Darío (Revista de Historia Social y de las Mentalidades, 2020)
This article studies the modes of reading and use of the documents of the archive of the Police Intelligence Directorate of the Province of Buenos Aires (DIPBA) in the scientific-academic field. Using a corpus of scientific research articles, we investigate the uses of this archive based on statistical analysis and reconstructing the topography of intertextual relationships between the documentation and the academic papers examined. Secondly, we analyze the modes of reading and presentation of the documentation registered in the discursiveness of the articles, focusing on the discursive and enunciative effects related to the use of the archive. As an initial approach to the grammars of recognition of the DIPBA archive, we describe some of the effects produced in the contemporary recognition of its documentation, in order to explore edges of the production of representations about the repression and the recent past in Argentina.
Keywords: Archive; DIPBA; Reading Modes; Usage Modalities